Inflammation-induced leg length discrepancy in children: from molecular mechanisms to clinical implications - Aeppli, Tim R. J.; Zhang, Zhengpei; Zhao, Yunhan; Zaman, Farasat; Sävendahl, Lars (Frontiers in Medicine, 2025)
Leg length discrepancy (LLD) refers to a condition where the lower limbs are of unequal length, which can result from various underlying causes. Inflammatory conditions in children, such as monoarticular, pauciarticular or polyarticular juvenile idiopathic arthritis (JIA), can lead to the development of LLD when predominantly affecting one leg. To date, no review has addressed inflammation-induced LLD. Depending on the localization of the inflammation and age of onset, bone growth can be either locally retarded or accelerated in the affected leg. The resulting LLD can range from mild forms, where treatment is not necessary, to severe forms, leading to premature growth plate fusion and/or an LLD of 5 cm or more. The overall aim of this review is to provide an overview of inflammation-induced LLD and to discuss the possible underlying mechanisms at the growth plate level. In addition, this review offers guidance regarding the natural course of the disease and explores potential new treatment strategies for patients with inflammation-induced LLD.